2019
DOI: 10.2298/ciceq180323025r
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical CO2 impregnation of Gelatin-Chitosan films with clove essential oil and characterization thereof

Abstract: is the first study on supercritical impregnation of G/Ch films with clove oil (CO) • CO in films was affected by CO2 pressure, impregnation time and G:Ch ratio • CO loading was favoured at 10-20 MPa, impregnation time of 2-6 h and Gwt% 25-50% • ScCO 2 treatment had the highest plasticizing effect on G/Ch50:50 • Thermal stability of the G/Ch film with 56 mg CO/g film to 110 °C was demonstrated Abstract Supercritical CO 2 impregnation process was used for the first time to fabricate biodegradable gelatin-chitosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 59 publications
(93 reference statements)
3
11
0
Order By: Relevance
“…This improvement on the film mechanical resistance was explained by the antiplasticization effect of rosemary volatile compounds in the polymer matrix as reported by Radović et al. (2019).…”
Section: Resultssupporting
confidence: 61%
“…This improvement on the film mechanical resistance was explained by the antiplasticization effect of rosemary volatile compounds in the polymer matrix as reported by Radović et al. (2019).…”
Section: Resultssupporting
confidence: 61%
“…As can be seen, non-impregnated SC and SCZ films exhibited a similar thermal profile with three decomposition stages. The initial weight loss at 52–60 °C corresponds to the loss of physically adsorbed water molecules, while the second step can be ascribed to the loss of strongly hydrogen-bonded water and glycerol used for the film preparation [ 56 ]. The most pronounced weight loss, followed by a peak at DTG with the maximum at ~290–300 °C, corresponds to complex decomposition processes of starch and chitosan, including the depolymerization of chains, dehydration and deamination of the saccharide rings [ 56 , 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…These values were in accordance with previously determined impregnation yields. The slight shift of the films’ degradation temperature to somewhat higher values indicates an improved thermal stability of impregnated films, which is explained by interactions between the polymer chains and the molecules of thymol [ 33 , 56 ]. Results showed that films impregnated with thymol are stable up to 100 °C, and are thus suitable for safe application in the food packaging industry.…”
Section: Resultsmentioning
confidence: 99%
“…Higher loading capacity of CG films were previously reported when clove oil was used. [ 19 ] Namely, depending on the SSI process conditions (40 °C, 10–30 MPa, 2–18 h), amounts of loaded clove oil in the CG films were in the range from 50 to 130 mg g −1 . [ 19 ] The difference in the loading values between reported findings and results of this study can be explained by the differences in process conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Various solid carriers were reported as suitable for SSI with bioactive agents. For example, metal–organic frameworks were impregnated with carvacrol, [ 16 ] cellulose acetate was impregnated with thymol [ 17 ] and pyrethrum extract, [ 18 ] gelatin‐chitosan was impregnated with clove essential oil, [ 19 ] poly(D,L‐lactic acid), [ 20 ] poly(D,L‐lactic‐co‐glycolic acid), [ 21 ] poly(D,L‐lactic acid)/poly( ε ‐caprolactone), [ 22 ] low density polyethylene nanocomposites, [ 23 ] and starch [ 14 ] were impregnated with thymol. However, there is only one report in available literature that describes utilization of SSI process for loading of TC mixture into poly(D,L‐lactic acid)/poly( ε ‐caprolactone).…”
Section: Introductionmentioning
confidence: 99%